Interaction of Refractory Dibenzothiophenes and Polymerizable Structures - Jose L. Rivera; Pedro Navarro-Santos; Roberto Guerra-Gonzalez; Enrique Lima (International Journal of Polymer Science)
We carried out first principles calculations to show that polymerizable structures containing hydroxyl (alcoholic chain) and amino groups are suitable to form stable complexes with dibenzothiophene (DBT) and its alkyl derivates. These sulfur pollutants are very difficult to eliminate through traditional catalytic processes. Spontaneous and exothermic interactions at 0 K primarily occur through the formation of stable complexes of organosulfur molecules with monomeric structures by hydrogen bonds. The bonds are formed between the sulfur atom and the hydrogen of the hydroxyl group; additional hydrogen bonds are formed between the hydrogen atoms of the organosulfur molecule and the nitrogen atoms of the monomers. We vary the number of methylene groups in the alcoholic chain containing the hydroxyl group of the monomer and find that the monomeric structure with four methylene groups has the best selectivity towards the interaction with the methyl derivates with reference to the interaction with DBT. Even this study does not consider solvent and competitive adsorption effects; our results show that monomeric structures containing amino and hydroxyl groups can be used to develop adsorbents to eliminate organosulfur pollutants from oil and its derivates.